Klitih In The Digital Era: A Criminogenic Analysis And The Dilemma Of Restorative Justice Implementation - Hartanto, Hartanto (Universitas Slamet Riyadi, 2025)
The phenomenon of klitih in Yogyakarta represents a form of street violence perpetrated by adolescents, often rooted in complex criminogenic factors such as moral degradation, weak family control, the influence of social media, and the glorification of violence by peer groups. This study employs a descriptive qualitative approach through case analysis and an examination of structural, cultural, and systemic factors influencing juvenile delinquency. The implementation of restorative justice as regulated in Law No. 11 of 2012 on the Juvenile Criminal Justice System is deemed ineffective in providing a deterrent effect, particularly in cases of recidivism that neglect the rights of victims. Data from concrete cases indicate patterns of violent behaviour driven by alcohol consumption, possession of sharp weapons, and parental neglect. Social media exacerbates the situation by serving as a medium for glorifying violence and coordinating actions. Therefore, reform of the juvenile justice system is necessary, combining rehabilitative approaches with firm sanctions, especially for repeat offenders. Additionally, digital campaigns promoting counter-narratives to youth violence must be intensified.